Whole-Exome Sequencing on Circulating Tumor Cells Explores Platinum-Drug Resistance Mutations in Advanced Non-small Cell Lung Cancer - Chang, Yuanyuan; Wang, Yin; Li, Boyi; Lu, Xingzhong; Wang, Ruiru; Li, Hui; Yan, Bo; Gu, Aiqin; Wang, Weimin; Huang, Aimi; Wu, Shuangxiu; Li, Rong (Frontiers in Genetics, 2021)
Circulating tumor cells (CTCs) have important applications in clinical practice on early tumor diagnosis, prognostic prediction and treatment evaluation. Platinum-based chemotherapy is a fundamental treatment for non-small cell lung cancer (NSCLC) patients who are not suitable for targeted drug therapies. However, most patients progressed after a period of treatment. Therefore, to reveal the genetic information contributing to drug resistance and tumor metastasis in CTCs is valuable for treatment adjustment. In this study, we enrolled 9 NSCLC patients with platinum-based chemotherapy resistance. For each patient, 10 CTCs were isolated when progression occurred to perform a single cell-level whole-exome sequencing (WES). Meanwhile the patients’ paired primary-diagnosed formalin-fixed and paraffin-embedded (FFPE) samples and progressive biopsy specimens were also performed WES. Comparisons of distinct mutation profiles between primary and progressive specimens, as well as CTCs reflected that different evolutionary mechanisms between CTC metastasis and lymph node metastasis, embodied in more proportion of mutations in CTCs shared with paired progressive lung tumor and hydrothorax specimens (4.4%-33.3%) than with progressive lymphatic node samples (0.6%-11.8%). Functional annotation showed that CTCs not only harboured cancer driver gene mutations, including frequent mutations of EGFR and TP53 shared with primary and/or progressive tumors, but also particularly harboured cell cycle-regulated or stem cell-related gene mutations, including SHKBP1, NUMA1, ZNF143, MUC16, ORC1, PON1, PELP1, etc. most of which derived from primary tumor samples and played crucial roles in chemo-drug resistance and metastasis for NSCLCs. Thus, detection of genetic information in CTCs is a feasible strategy for drug resistance study and new drug target discovery when progressive tumor specimens were unavailable.